2018
DOI: 10.1029/2018je005693
|View full text |Cite
|
Sign up to set email alerts
|

Lunar Cryptomare: New Insights Into the Balmer‐Kapteyn Region

Abstract: Cryptomaria record the early mare volcanisms and put important constraints on the lunar thermal and volcanic history and on the early partial melting of the mantle. This work focuses on the representative cryptomare region of Balmer‐Kapteyn and employs multisource exploration data including Lunar Reconnaissance Orbiter Camera Wide Angle Camera, Lunar Reconnaissance Orbiter Camera Narrow Angle Camera, Lunar Orbiter Laser Altimeter Digital Elevation Model (DEM), GLD 100, Chang'E‐1 Interference Imaging Spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 53 publications
2
15
1
Order By: Relevance
“…Hawke et al (2005) indicated that some of the buried mare basalts may be high-alumina (Al 2 O 3 > 11 wt.%) mare basalts in the B-K region. Wang & Qiu (2018) further verified that almost all the buried mare basalts in this region may be high-alumina ones through the measurement results of dark-haloed crater (DHC). Whitten & Head (2015a) analyzed the mineral content using the Moon Mineralogy Mapper (M 3 ) in the B-K region, and further concluded that only the mare basalts of the ancient igneous rocks are consistent with the cryptomaria in absorption band centers and FeO and Th concentrations.…”
Section: Introductionsupporting
confidence: 57%
See 4 more Smart Citations
“…Hawke et al (2005) indicated that some of the buried mare basalts may be high-alumina (Al 2 O 3 > 11 wt.%) mare basalts in the B-K region. Wang & Qiu (2018) further verified that almost all the buried mare basalts in this region may be high-alumina ones through the measurement results of dark-haloed crater (DHC). Whitten & Head (2015a) analyzed the mineral content using the Moon Mineralogy Mapper (M 3 ) in the B-K region, and further concluded that only the mare basalts of the ancient igneous rocks are consistent with the cryptomaria in absorption band centers and FeO and Th concentrations.…”
Section: Introductionsupporting
confidence: 57%
“…However, this method has some limitations: (1) some exposed mare surrounding DHCs may be pyroclastic material or deposits of low-albedo impact melt (Hawke & Head 1977;Hawke et al 1989Hawke et al , 2005Schultz & Spudis 1979); (2) the image quality may affect DHC recognition, mistaking terrain shadows for DHC (Wang & Qiu 2018); ( 3) not all excavated mare basalts showed complete dark-haloed feature (most dark deposits occur only in or around the crater and do not appear annular). To overcome these problems, in this work, the criteria for cryptomare determination include the following conditions: (1) the presence of a high Fe content area (FeO > 12 wt.%, Northeast Africa 001-B1B is the sample of mare basalt with the lowest content of FeO, 12.21 wt.%; Snape et al 2011) determined from the FeO abundance maps;…”
Section: Cryptomare Identificationmentioning
confidence: 99%
See 3 more Smart Citations